2009
DOI: 10.3892/ijo_00000409
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping of diffuse large B-cell lymphoma (DLBCL) defines multiple sub-groups of germinal centre-like tumours displaying different survival characteristics

Abstract: Abstract. Diffuse large B-cell lymphoma (DLBCL) forms a heterogeneous collection of aggressive non-Hodgkin's Lymphoma in which three principle classes of neoplasia have been defined according to gene expression and immunophenotyping studies. The present investigation sought to examine the immunophenotype of proposed subgroups and relate these to patient survival. A series of 155 DLBCL treated uniformly with anthracycline therapy in clinical trials, were stratified upon the basis of common biomarker expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…This analysis also successfully re-identified many genes that have previously been shown to be biomarkers for each DLBCL subtype (Rosenwald et al 2002; Tirado et al 2012), including BCL2 , IRF4 , MME ( CD10 ), and BCL6 (Table 2). Surprisingly, the established ABC subtype biomarker MUM1 (Hans et al 2004; Sweetenham 2005; Anderson et al 2009) showed no significant expression change (FDR = 0.92) but did have a STAT3 BR 344 bp upstream of its TSS with significantly more binding in GCB (fold change = 0.46, FDR = 4.89 × 10 −3 ).…”
Section: Resultsmentioning
confidence: 99%
“…This analysis also successfully re-identified many genes that have previously been shown to be biomarkers for each DLBCL subtype (Rosenwald et al 2002; Tirado et al 2012), including BCL2 , IRF4 , MME ( CD10 ), and BCL6 (Table 2). Surprisingly, the established ABC subtype biomarker MUM1 (Hans et al 2004; Sweetenham 2005; Anderson et al 2009) showed no significant expression change (FDR = 0.92) but did have a STAT3 BR 344 bp upstream of its TSS with significantly more binding in GCB (fold change = 0.46, FDR = 4.89 × 10 −3 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, most of these methods are not routinely used because of the substantial cost, technical complexity, and the requirement for fresh or frozen tissue. [4][5][6][7][8] In the present study, we attempted to evaluate whether immunohistochemical parameters (p53, Bcl-2, Bcl-6, and MUM1) are useful for determining the prognosis of patients with DLBCL after second-line treatment. None of the immunohistochemical parameters evaluated achieved statistical significance in our study, probably because of the small number of patients in the analysis set.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Recent studies have also attempted to define these groups using immunohistochemistry markers, such as B-cell lymphoma 6 (Bcl-6) and CD10 for the germinal center, and multiple myeloma 1 (MUM1), interferon regulatory factor 4, and CD38 for the postgerminal center. [6][7][8] Despite the fact that many clinical factors and biomarkers have been evaluated to predict the prognosis of patients with DLBCL, the International Prognostic Index (IPI) remains the easiest to apply and the most recognized index. The IPI is based on the evaluation of 5 clinical factors: age > 60 years, Ann Arbor stage III or IV disease, > 1 extra nodal site, European Cooperative Oncology Group performance status (ECOG PS) !…”
Section: Introductionmentioning
confidence: 99%
“…IHC was performed using the automated Ventana BenchMark ® immunostaining system. Full details of conditions were described previously (24). All DLBCL cell lines were segregated on the basis of their immunophenotype and classified as either GC-like or ABC-like, based on the algorithm proposed by Hans et al (8).…”
Section: Methodsmentioning
confidence: 99%